The concept of “loneliness” in the conceptual and linguistic picture of the world (based on the works of S. Zhunissov) - Rakymzhan, О.Қ.; Berdibaу, Ш. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2022)
The analysis of literary texts allows us to characterize the component of the collective, national experience of cognition of the world by identifying the features of the conceptual system of a particular writer. The article analyzes the manifestations of the concept in various discourses during the study of the concept of “loneliness” as a communicative and discursive unit in the works of the writer S. Zhunissov. Its content and forms of manifestation in consciousness are determined, linguistic and cognitive mechanisms of actualization are revealed. Through the artistic interpretation of the information stored in the writer's cognitive system and the identification of the specifics of understanding, the semantic field of the artistic concept is revealed. That is, the conceptual core of the concept of “loneliness” is determined. The concept of “loneliness” has always seemed to be a capacious cultural symbol, as well as a symbol of the human condition in an era of social, moral and metaphysical crisis, as well as the real state of man in the world as a whole. Indeed, being the direction of the main problems of human life, the problem of loneliness, in fact, is a human problem. This study explores the thematic scope of existential loneliness studied by novelists, poets and writers to conclude the preparation of each linguistic metaphor for which it is difficult to define an intercultural stylometric signature, basic conceptual metaphors and existential loneliness. The research paper analyzes that the concept of loneliness has the properties of an emotional, universal, regulatory, basic concept. We see the prospects for research in the further study of the concept in other types of discourse, the expansion of the research material, the deepening of discourse and concept in their relationship. In addition, the study of the concept of loneliness can serve as a basis for the study of concepts that are close in semantic content to it, but have a narrow range of phenomena covered.